A System-Based Comparison of Gene Expression Reveals Alterations in Oxidative Stress, Disruption of Ubiquitin-Proteasome System and Altered Cell Cycle Regulation after Exposure to Cadmium and Methylmercury in Mouse Embryonic Fibroblast - Yu, Xiaozhong; Robinson, Joshua F.; Sidhu, Jaspreet S.; Hong, Sungwoo; Faustman, Elaine M. (Toxicological sciences, 2010)
Environmental and occupational exposures to heavy metals such as methylmercury (MeHg) and cadmium (Cd) pose significant health risks to humans, including neurotoxicity. The underlying mechanisms of their toxicity, however, remain to be fully characterized. Our previous studies with Cd and MeHg have demonstrated that the perturbation of the ubiquitin-proteasome system (UPS) was associated with metal-induced cytotoxicity and apoptosis. We conducted a microarray-based gene expression analysis to compare metal-altered gene expression patterns with a classical proteasome inhibitor, MG132 (0.5μM), to determine whether the disruption of the UPS is a critical mechanism of metal-induced toxicity. We treated mouse embryonic fibroblast cells at doses of MeHg (2.5μM) and Cd (5.0μM) for 24 h. The doses selected were based on the neutral red–based cell viability assay where initial statistically significant decreases in variability were detected. Following normalization of the array data, we employed multilevel analysis tools to explore the data, including group comparisons, cluster analysis, gene annotations analysis (gene ontology analysis), and pathway analysis using GenMAPP and Ingenuity Pathway Analysis (IPA). Using these integrated approaches, we identified significant gene expression changes across treatments within the UPS (Uchl1 and Ube2c), antioxidant and phase II enzymes (Gsta2, Gsta4, and Noq1), and genes involved in cell cycle regulation pathways (ccnb1, cdc2a, and cdc25c). Furthermore, pathway analysis revealed significant alterations in genes implicated in Parkinson’s disease pathogenesis following metal exposure. This study suggests that these pathways play a critical role in the development of adverse effects associated with metal exposures.